Optimising flight connection times in airline bank structure through Simulated Annealing and Tabu Search algorithms - Ciftci, Muharrem Enis; Ozkir, Vildan (ELSEVIER SCI LTD, 2020)
In hub and spoke airline networks, flight arrivals and departures generally have a bank structure to increase connections among spoke cities through a hub airport in order to provide cheaper service for higher volumes of air traffic. In this study, we introduce the airline bank optimisation problem with a novel mathematical model for improving flight connection times. The mathematical model aims to minimise the total connection times for transfer passengers and generates flight schedules regarding slot capacities in the hub airports. Since the problem is a combinatorial optimisation problem NP-hard and computational complexity increases rapidly for real-world problems, we employ the simulated annealing and the tabu search algorithms to achieve better solutions in a reasonable time. We generate sub-problems using real-world data and investigate the effectiveness of the algorithms. Finally, we present the results of a real case study of a Turkish airline company which has a hub airport connecting the flights between Middle Eastern and European cities.
Keywords: Hub and spoke systems; Flight rescheduling; Tabu search; Simulated annealing; Airline bank structure; SLOT ALLOCATION; NETWORK; HUB; COMPETITION; OPTIMIZATION; PERFORMANCE; ECONOMIES; EVOLUTION; DENSITY; SERVICE; Transportation